Formulation and Activity of Sunscreen Cream from Ethanol Extract of Calendula officinalis L Flowers - Rohmani, Sholichah; Mar’atushsholihah, Luthfia; Darojati, Ulfa Afrinurfadhillah; Meitasari, Annisa Diyan; Susanto, Bela Novita Amaris (Fakultas Farmasi Universitas Andalas, 2024)
Sunscreen made of natural ingredients is an alternative to protect the skin from excess UV radiation and a substitute for chemical products that have side effects. It was reported that Calendula officinalis L. has flavonoid and saponin metabolite compounds which function as photoprotective agents. This research aims to formulate sunscreen cream and examine the effect of variations in Calendula officinalis L flower extract (5%;7%;10% w/v) on physicochemical properties, stability, and values of the Sun Protecting Factor (SPF) in vitro using UV-Vis spectrophotometry and in vivo using wistar line rat test animals to see the time of formation of Minimum Erythema Dose (MED). It has been proven that variations in the concentration of Calendula officinalis L. extract affected the physicochemical properties, such as pH value, viscosity, spreadability, and adhesion strength. However, the overall results of the physicochemical properties still met the requirements. Variations in extract concentration affected the SPF value. In vitro SPF test showed the minimum protection category for F1, extra protection for F2, maximum protection for F3, and no protection for F0. Meanwhile, the in vivo SPF test showed the minimal protection category for F1, medium protection for F2, extra protection for F3, and no protection for F0.